Averaging of boundary-value problems of control over a standard system with delay - Efendiev, V. V.; Zheltikov, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For the terminal problem of optimal control over systems of standard form with constant delay, according to the Pontryagin maximum principle, we study a boundary-value problem with deviating arguments with delay and anticipation. We justify an averaging method for an asymptotic solution of the boundary-value problem obtained.